Adhesion Strength of Wood Based Composites Coated with Cellulosic and Polyurethane Paints. (25th May 2015) - Dilik, Tuncer; Erdinler, Seda; Hazır, Ender; Koç, Hüseyin; Hiziroglu, Salim
Abstract : The objective of this study was to determine adhesive strength of particleboard and medium density fiberboard (MDF) finished with two types of paints. Samples were coated using cellulosic and polyurethane based paints. Adhesion strength and coating layer thickness of each sample were measured using pull-off testing method and PosiTector equipment, respectively. The highest adhesion strength value of 3.62 MPa was found for MDF samples coated with paint. Based on the statistical analysis type of substrate significantly influenced overall adhesion strength of the samples while type and layer thickness of paint as well as number of layers applied to the surface of specimens have not affected significantly adhesion resistance of the panels used in this work. It appears that pull-off test can effectively be used to determine and evaluate adhesion strength of the samples considered in the experiments.